Reactivity of a glassy and a crystalline Fe66Cr10Nb5B19 alloy towards aluminum during sintering: a comparative study - Kvashnin, Vyacheslav I.; Dudina, Dina V.; Bokhonov, Boris B.; Petrov, Sergey A.; Ukhina, Arina V.; Georgarakis, Konstantinos; Coury, Francisco Gil; Koga, Guilherme Yuuki (Elsevier, 2023)
A glassy Fe66Cr10Nb5B19 alloy and its crystalline counterpart consisting of the α-(Fe,Cr), FeNbB and Fe2B phases were spark plasma sintered with aluminum at 570 °C to investigate the interfacial reactions in the systems. In the mixture containing the crystalline alloy, α-(Fe,Cr) and Fe2B reacted with aluminum forming the Fe-Al intermetallic reaction products. The crystallites of FeNbB were distributed in the intermetallic matrix. The absence of α-(Fe,Cr) and Fe2B in the composite sintered from the glassy alloy was confirmed by Mössbauer spectroscopy. Overall, under the short SPS processing, the crystalline alloy was found to be more reactive towards aluminum than the glassy alloy. An increased reactivity was due to the presence of α-(Fe,Cr), a Fe-rich phase, in the crystalline alloy.
Keywords: Metallic glass; Aluminum; Intermetallic; Reactivity